Effects of a vinasse-microorganism blend application on a vertisol with sugarcane (2012)
The effect of a second dose of vinasse on some physical and chemical properties of a Vertisol was evaluated with cut sugarcane in Valle del Cauca, Colombia. We analyzed the expression of any possible toxicity in foliar tissue samples at the end of the cycle. Vinasse treatments added with two different mixtures of microorganisms were established in a randomized complete block with five replicates: soil without vinasse and no microorganisms; soils with a dose of vinasse, soils with two doses of vinasse; soils with a single dose of vinasse separately evaluated with two different mixtures of microorganisms and soils with two doses of vinasse separately evaluated with two different mixtures of microorganisms. The chemical properties evaluated were pH, soil organic matter content, C, N, P, Ca, Mg, Na, and K content, cation exchange capacity CEC and electrical conductivity EC. The physical properties determined were bulk density, particle density and porosity. There were no significant differences in the physical and chemical properties of the soil for the evaluated cultivation cycle with the application of one or two doses of vinasse with and without microorganisms. Leaf tissue analysis did not show a nutritional imbalance due to the second application.